The molecular mechanism of photochromism in photo-enolizable quinoline and napthyridine derivatives - Knippenberg, Stefan; Schneider, Matthias; Dreuw, Andreas (The journal of physical chemistry. A, Molecules, clusters, and aerosols, 2012)
Photochromism, the change of color upon irradiation, is a general property of quinoline derivatives, yet subtle differences in the geometric structure influence its occurrence. To investigate this relation, the mechanism of photoenolization of the photochromic compounds 3-benzoyl-2-benzyl-1-methyl-1H-quinoline-4-one (1) and 3-benzoyl-1,2-dibenzyl-1H-1,8 naphtyridin-4-one (2) as well as of the structurally closely related but nonphotochromic 3-benzoyl-1-benzyl-2-methyl-1H-1,8-naphtyridin-4-one (3) has been investigated theoretically using state-of-the-art quantum chemical methods. Focusing on the difference between 2 and 3 and stressing the absence of a phenyl group in the latter, the excited state potential energy surfaces along the photoenolization coordinate have been calculated for both. While the initial proton transfer initializing photoenolization is feasible when the phenyl group is present in 1 and 2, it is suppressed in 3.